Perfil físico-químico, químico e sensorial de cafés especiais do Cerrado Mineiro - Tavares, Katiany Mansur (2016)
The coffee quality is narrowly related with its flavor and aroma characteristics that are developed during the roasting process. Such characteristics are strongly influenced by the raw grain chemical composition that may vary according to the influence of various factors, as cultivation place, variety, crop management and procedures adopted during and after harvest. Coffee has an extremely complex chemical composition, consisting of several volatile and non-volatile compounds, many of which are generated in the thermal reactions that occur during grain roasting. The ascendancy demand for specialty coffees, associated with the flavor and aromas diversity of coffees produced in Brazil, justifies studies on their chemical composition, aiming to establish a relationship between their constituents and the beverage sensorial profile. Therefore, the objective of this study was to evaluate the chemical composition and volatile profile of Cerrado Mineiro special coffee and its influence on the beverage sensorial attributes. Ten samples of special coffees from the Cerrado Mineiro region were evaluated, five of them from natural processing (A, B, C, D and E) and five from pulped coffee (F, G, H, I and J) regarding physical-chemical, sensorial and volatile profiles attributes. The results were analyzed through means tests (Scott-Knott) and principal components analysis (PCA). In the sensorial analysis, only the sample A distinguished significantly (p <0.05) from the other natural coffees regarding the sensorial attributes analyzed and the final note. The pulped coffee did not distinguished significantly in the final sensorial grade. The main volatile compounds identified in the coffees were furans, pyrazine, ketones, pyrroles, alcohols and aldehydes, regardless of the postharvest processing type. The PCA showed that the constituents that contributed the most to the discrimination of sample A with the highest sensorial grade among natural coffees were caffeine, trigonelline, stearic acid, alcohols, pyrroles, ketones and pyrazines. The sample F discriminated from the other pulped coffee and the constituents that most contributed to its distinction were titratable acidity, 5-caffeoylquinic acid, trigonelline, ashes, palmitic and linoleic acids, as well as pyrazines, phenols and ketones.